Human Antibodies Specific for the High-Molecular-Weight Adhesion Proteins of Nontypeable Haemophilus influenzae Mediate Opsonophagocytic Activity - Winter, Linda E. (American Society for Microbiology, 2003)
The HMW1- and HMW2-like adhesion proteins of nontypeable Haemophilus influenzae are expressed by 75% of these strains, and antibodies directed against these proteins are protective in animal models of infection. The purpose of the present study was to define the functional activity of human antibodies specific for these proteins in an in vitro complement-dependent opsonophagocytic assay. Human promyelocytic cell line HL-60 served as the source of phagocytic cells, and a commercial preparation of intravenous immunoglobulin (IVIG) served as the source of human antibodies. High-molecular-weight (HMW) proteins were purified from four prototype nontypeable H. influenzae strains and used to prepare solid-phase affinity columns. IVIG was adsorbed on each column to remove strain-specific anti-HMW antibodies and to allow recovery of affinity-purified anti-HMW antibody fractions. Unadsorbed IVIG killed each of the prototype strains at titers of 1:80 to 1:320. HMW-adsorbed sera demonstrated fourfold decreases in opsonophagocytic titer against the homologous strains compared to unadsorbed IVIG. Affinity-purified anti-HMW antibody preparations demonstrated opsonophagocytic titers of 1:20 to 1:80 against the respective homologous strains and opsonophagocytic titers as high as 1:80 against heterologous strains. None of the affinity-purified anti-HMW antibody preparations was opsonophagocytic for a representative nontypeable H. influenzae strain that did not express HMW1- or HMW2-like proteins. These data demonstrate that human antibodies specific for the HMW1/HMW2-like adhesion proteins of nontypeable H. influenzae are opsonophagocytic and that such antibodies recognize epitopes shared by the HMW proteins of unrelated nontypeable H. influenzae strains. These results argue for continued investigation of the HMW1/HMW2-like proteins as potential vaccine candidates for prevention of disease due to nontypeable H. influenzae.